Reimagining alternative technology for design in the 21st century - Kennedy, Brook S. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Reimagining Alternative Technology for Design in the 21st Century proposes a new approach to design that harnesses still-valuable alternative, traditional and abandoned technologies over the creation of new ones to address contemporary global concerns. It focuses on design concepts that reduce energy and material consumption to tackle issues such as climate change and pollution in industrialised economies. The book takes the reader on a journey surveying different facets of human activity to identify concrete opportunities where underused and discarded technologies could be indispensable today. It critically addresses newer approaches to design and technology by comparing them to existing alternatives, unpacking examples including air-conditioning with smart thermostats, electric lighting, durable reusable products, domestic maintenance tools, and methods of transportation. Written for practicing designers and students in industrial design, architecture, sustainable design, and human-centred design, this book provides new ideas and tools for creating more useful, energy-and-resource-efficient product designs and systems"--
Keywords: Technological innovations; Appropriate technology; Technological forecasting; Sustainable design; Product design; System design; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Interior Design / General